The effects of substitution of hospital ward care from medical doctors to physician assistants on non-adherence to guidelines on medication prescribing - Bos, Jacqueline M.; Timmermans, Marijke J. C.; Kalkman, Gerard A.; Bemt, Patricia M. L. A. van den; Smet, Peter A. G. M. De; Wensing, Michel; Kramers, Cornelis; Laurant, Miranda G. H. (PLOS ONE, 2018)
Aim: This study determined the effect of substitution of inpatient care from medical doctors (MDs) to physician assistants (PAs) on non-adherence to guidelines on medication prescribing. Methods: A multicenter matched-controlled study was performed comparing wards on which PAs provide medical care in collaboration with MDs (PA/MD model), with wards on which only MDs provide medical care (MD model). A set of 17 quality indicators to measure non-adherence to guidelines on medication prescribing by PAs and MDs was composed by 14 experts in a modified Delphi procedure. The indicators covered different pharmacotherapeutic subjects, such as gastric protection in case of use of NSAID or prevention of obstipation in case of use of opioids. These indicators were expressed in proportions by dividing the number of patients in which the prescriber did not adhere to a guideline, by all patients that were applicable. Multivariable regression analysis was performed in order to adjust for potential confounders. Results: 1021 patients from 17 hospital wards in the ‘PA/MD model’ group and 1286 patients from 17 hospital wards in the ‘MD model’ group were included. Two of the 17 quality indicators showed significantly less non-adherence to guidelines for the PA/MD model; the indicators concerning prescribing gastric protection in case of use of NSAID in combination with corticosteroids (OR 0.42, 95% CI 0.19-0.90) and in case of use of NSAID in patients older than 70 years (OR 0.47, 95% 0.23-0.95). For none of the other quality indicators for prescribing of medication a difference between the MD model and the PA/MD model was found. Conclusion: This study suggests that the non-adherence to guidelines on medication prescribing on wards with the PA/MD model does not differ from wards with traditional house staffing by MDs only. Further research is needed to determine quality, efficiency and safety of prescribing behavior of PAs.